Sustainability impacts of ecosystem approaches to small‑scale aquaculture in Bangladesh - Rossignoli, Cristiano (2025)
Aquatic food is vital for food security in Bangladesh, where fish accounts for up to 60% of animal-based protein intake. As the world’s 5th largest aquaculture producer, the sector has expanded significantly, supporting livelihoods and food security. Small-scale aquaculture, particularly in inland ponds, dominates production, contributing 94% of national output. Around 4.3 million rural households (20% of the population) manage homestead ponds, typically 0.08–0.10 hectares in size. This presentation introduces the EcoPond Model, along with the methodology and key findings, highlighting how ecosystem-based approaches enhance sustainability, improve resource efficiency, support biodiversity, and strengthen climate resilience in small-scale aquaculture.